POTENSI FORMULASI BAKTERI PEREDUKSI NITRAT WADUK SUTAMI MALANG DALAM MENGHAMBAT PERTUMBUHAN Microcystis - C. Retnaningdyah; U. Marwati; Suharjono Suharjono; N. Ajijah; Marjono Marjono; A. Soegianto; B. Irawan (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
The problem facing in water ecosystem espescially reservoir in Indonesia is the blooming of Microcystis. The specific objective of this research was to determined the ability of indigenous bacteria formulation from Sutami reservoir, which be known have a capability of reducing nitrate, to controlled Microcystis growth. The research methodology as follow: the bacteria formulation was isolated from Sutami reservoir that had been tested having potency to reduce nitrate, than we carried out to examine the effect of that bacteria formulation toward the growth rate of Microcystis. This experiment have been done in laboratory. The formula of bacteria and Microcystis were grown together in sterilized natural media from Sutami reservoir adding with NO3-N 5 ppm. The treatment of this research were aeration and non aeration and variation of light intensity (2–3 Klux and 5–9 Klux). Incubation was done in laboratory with constant light for 12 hours per day. The abundance of Microcystis and bacteria were counted every day for 13 days. Then, the environment parameters such as pH, conductivity, concentration of nitrate, nitrite and ammonium were measured every weeks. The experiment was done with three replications at the same time using completely randomized design. The research result showed that there were found 22 species of bacteria capable to reduce nitrate in selective media, but only six species have highest potency to reduce nitrate more than 90%. The consortium of the six bacteria with abundance 4 × 107 cell/mL able to controlled the growth of Microcystis in laboratory 80–95% be started at sixth day after incubation. The bacteria consortium was found in this research can be recommended to used as bioagent active to controlled Microcystis blooming in the water if culturing of these bacteria utilize medium having no potency as source of pollutant in the water.